Assessing the influencing factors of out-of-pocket costs on tuberculosis in Sichuan Province: a cross-sectional study - Lan Xia; Lijie Gao; Yin Zhong; Ya Wu; Jinge He; Fengjuan Zou; Ronghua Jian; Sujian Xia; Chuang Chen; Sui Zhu (BMC Public Health, 2023)
Abstract Background Although diagnosis and treatment services for tuberculosis (TB) are provided free of charge in most countries, direct non-medical and indirect costs due to absenteeism, also place a significant burden on patients and their families. Sichuan Province has the second highest incidence of TB in China, with an incidence of approximately 100 cases per 100 000 people. However, there are limited research on out-of-pocket expenditure (OOPE) and its influencing factors in TB patients in Sichuan Province. Methods A retrospective cross-sectional study was conducted on TB patients in designated medical institutions for TB in Sichuan Province from 2017-2021. A face-to-face questionnaire was conducted to obtain the information related to hospitalization of patients, and the multi-level regression model was used to analyse the factors that influence OOPE and total out-of-pocket expenditure (TOOPE) of TB patients. Results A total of 2644 patients were investigated, and 74.24% of TB patients and their families experienced catastrophic total costs due to TB. The median total cost was 9223.37 CNY (1429.98 USD), in which the median direct and indirect costs of TB patients were 10185.00 CNY (1579.07 USD) and 2400.00 CNY (372.09 USD), respectively, and indirect costs contributed to 43% of total costs. The median OOPE and TOOPE costs were 6024.00 CNY (933.95 USD) and 11890.50 CNY (1843.49 USD), respectively. OOPE and TOOPE had common influencing factors including whether the patient's family had four or more members, a history of hospitalization, combination with other types of TB, the number of visits before diagnosis, and co-occurrence with chronic disease. Conclusions The OOPE and TOOPE for TB patients and their families in Sichuan Province are still heavy. In the long run, it is necessary to strengthen education and awareness campaigns on TB related knowledge, disseminate basic medical knowledge to the public, improve healthcare-seeking behavior, and enhance the healthcare infrastructure to improve the accuracy of TB diagnosis and reduce the significant OOPE and TOOPE faced by TB patients and their families in Sichuan Province.